POLITENESS PRINCIPLE: PRESIDENT JOKO WIDODO'S SPEECH ACT IN VIDEO BLOG - Risa Mufliharsi; Heppy Atma Pratiwi (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2019)
ABSTRACT The aim of the research is analyzing the utterances of Mr. Joko Widodo as president of Indonesia with vloggers. In this study, the writer analyzes the rules of president conducting his utterances at vloggers’ vlogs. The vlogs taken from skinnyindonesian24 which has 1.3M subscribers and Arif Muhammad which has 1.5M subscribers (data per November 25, 2018). The data taken and analyzed both qualitative and quantitative data. The elaboration of the methods used to measure language politeness, to count the data whether politenes or not. The data taken from Arif Muhammad’s vlog (1.596.033 subscribers) which entitle Ngevlog bareng Presiden and SkinnyIndonesian24 were created by brothers Andovi da Lopez and Jovial da Lopez’s vlogwho have 1.344.548 subscribers entitleHow to Become a President. The result of this research imply both of the vlogs Mr. Joko Widodo applies politeness strategies even in informal situation both vlogs. He acts extraordinary pragmatic forces and high politeness. So that, the audience gets the emotion, sympathy and persuasion of those who watches of them at vlog. Keywords: politeness principal, speech acts, vlog, pragmatics